INCREASING FLUX DENSITY BY HTS SHIELDING PELLET IN SUPERCONDUCTING SYNCHRONOUS MACHINE BASED ON FLUX CONCENTRATION - BOUMARAF, R.; M. MIMOUNE, S.; ALLOUI, L.; L. KHENE, M. (Courrier du Savoir, 2014)
In this paper, we propose a solution which enhances the performance of the inductor in high-power superconducting synchronous machines based on the flux concentration. The work is done by keeping the same topology and using a high temperature superconducting shielding pellet located between the two coils of the inductor. This pellet permits to recover the magnetic field which vanishes in the medium region due to the opposite direction of the coils. We did a 3D magnetostatic field analysis using the control volume method with unstructured grid. This analysis showed that the suggested solution allowed obtaining a maximum efficiency of about 8% in the flux density.